Adjuvant doxycycline to enhance anti-amyloid effects: Results from the dual phase 2 trial - D'Souza, Anita (EClinicalMedicine, 2020)
BACKGROUND: Although, doxycycline use is associated with improved outcomes in amyloidosis in retrospective studies, evidence from clinical trials is limited. METHODS: This phase 2 trial of doxycycline (clinicaltrials.gov: NCT02207556) in newly diagnosed light chain (AL) amyloidosis enrolled 25 patients with systemic AL amyloidosis on treatment with doxycycline for 1 year along with chemotherapy. Outcomes of interest included mortality, organ response, and hematologic response rates at 1 year. FINDINGS: The median age was 62 years, 64% were male, and 68% had the AL lambda subtype. Patients had Mayo 2012 stage 3 in 24% and stage 4 in 28%. Cardiac involvement was present in 60% of patients, renal involvement in 72%, and 60% patients had 3 or more organs involved. Target organ was cardiac in 14(56%), renal in 7(28%), hepatic in 1(4%) and soft tissue in 3(12%). At 1 year, mortality was 20% (95% confidence interval, 8.9–41.6%) and organ response was 36% (18–57%). Hematologic response in 1-year survivors was 100%, including 30% complete and 55% very good partial response. Autologous hematopoietic cell transplant was performed in 60%; among transplanted patients, day-100 transplant-related mortality was 0. Doxycycline use was safe and not attributed to any grade 2 or higher toxicity. INTERPRETATION: In addition to a low 1-year mortality, doxycycline use was safe and associated with high transplant utilization rate. We thus contend that doxycycline should be studied in a placebo-controlled study in newly diagnosed AL patients in the first year, particularly among patients with advanced disease and cardiac involvement.